2020
DOI: 10.1088/1755-1315/462/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-glucosidase inhibitory activities of bungur (Lagerstroemia loudonii Teijsm. & Binn.) leaves and fruits

Abstract: Bungur ( Lagerstroemia loudonii Teijsm. & Binn.) belongs to the Lytrhaceae that traditionally was used as antidiabetic, antiinflammatory, antihypertensive and diuretic. Other bungur plants such as Lagerstroemia speciosa have been known for the activity as alpha-glucosidase inhibitor. Based on chemotaxonomy, the distribution of compounds in one family or genus and its activity has similarities, then tested for the activity of alpha-glucosidase of Lagerstroemia loudonii Teijsm. & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…A previous Kolakul and Sripanidkulchai (2017) study reported that L. speciosa contains phenolic groups such as ellagic acid, epicatechin gallate, and gallic acid. In addition, a previous study by Riyanti et al (2020) reported Lagerstroemia loudonii Teijsm. & Binn exhibited inhibitory activity against yeast α-glucosidase.…”
Section: In Vitro Antidiabetic Activitymentioning
confidence: 91%
“…A previous Kolakul and Sripanidkulchai (2017) study reported that L. speciosa contains phenolic groups such as ellagic acid, epicatechin gallate, and gallic acid. In addition, a previous study by Riyanti et al (2020) reported Lagerstroemia loudonii Teijsm. & Binn exhibited inhibitory activity against yeast α-glucosidase.…”
Section: In Vitro Antidiabetic Activitymentioning
confidence: 91%
“…Aktivitas penghambatan alfaglukosidase ekstrak etanol daun bungur yang gugur lebih besar dibandingkan dengan ekstrak etanol daun bungur yang masih berwarna hijau dan fraksi air daun bungur yang gugur memberikan aktivitas penghambatan alfa-glukosidase yang terbesar dengan IC50 134,27 µg/mL. Riyanti et al, 2020). Selain itu dari daun bungur baik yang masih berwarna hijau ataupun yang gugur berwarna kuning dilaporkan memiliki aktivitas antioksidan dengan nilai nilai IC50 berturut-turut sebesar 7,53 µg/ml; dan 25,87 µg/ml (Soraya Riyanti & Windyaswari, 2019).…”
Section: Abstrakunclassified
“…In addition to the high ornamental value, L. loudonii also has medicinal value, with its leaves being used in traditional medicine to treat diabetes, inflammatory, and obesity in East Asia (Riyanti et al. 2020 ). At present, the research of L. loudonii is mainly focused on chemical constituents and pharmacology.…”
mentioning
confidence: 99%